Effect of gelatin/agar bilayer film incorporated with TiO2 nanoparticles as a UV absorbent on fish oil photooxidation. (15th May 2017) - Vejdan, Akbar; Ojagh, Seyed Mahdi; Abdollahi, Mehdi
Abstract: This research evaluated the effect of gelatin/agar bilayer film and nanocomposites containing different concentrations of TiO2 nanoparticles (0.5%, 1% and 2%) as ultraviolet (UV) and oxygen barriers on the oxidative stability of fish oil. Samples of fish oil covered with the bilayer films were stored under UV light or in darkness and with or without lids at 18 °C for 12 days. Oil quality in terms of peroxide values (PV), thiobarbituric acid (TBA), conjugated diene (CD), fatty acids profile and colour change (∆ E ) was monitored during storage. Fish oil photooxidation was hindered by increasing TiO2 concentration, so that nanocomposite containing 2% of the nanoparticles could control photooxidation, similar to the samples stored in darkness. Furthermore, upon studying both photooxidation and autoxidation, the highest amounts of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), as well as the lowest amount of changes in PV, TBA, CD and ∆ E, were observed in oils covered with the nanocomposites. Abstract : Schematic overview of fish oil packaging and storage (a) UV light permeability effect; (b) UV light and oxygen permeability effect.